糖尿病治療に伴い改善した特発性first bite syndromeの1例 - 石川, 純; 小間, 義朗; 南部, 和也; 安江, 玲太; 杉本, 圭佑; 藤本, 雄大 (日本口腔外科学会雑誌, 2021)
First bite syndrome (FBS) is a rare disease, characterized by sharp pain in the parotid region and jaw at the first bite of each meal, which is usually seen after surgical procedures involving the parapharyngeal space. We report a case of idiopathic FBS that improved with treatment of diabetes. The patient was a 59-year-old woman who had sharp pain in the left parotid region at the first bite of each meal. She had no surgical history involving the parapharyngeal space. Panoramic radiograph, CT, and MRI revealed no notable findings. During examination, a similar pain appeared in the right region. Bilateral idiopathic FBS was diagnosed and treatment with Goreisan was ineffective. A blood test revealed untreated severe diabetes (fasting blood sugar level: 261 mg/dL, HbA1c:14.2%), thus we referred her to a specialist. As the treatment of diabetes progressed, the idiopathic FBS symptoms improved gradually and the pain in the right region disappeared completely. At two years after initial diagnosis, her symptoms have almost resolved.